SMOFlipid Protects Preterm Neonates against Perinatal Nutrition–Associated Cholestasis - Kasirer, Yair; Bin-Nun, Alona; Raveh, Ateret; Schorrs, Irina; Mimouni, Francis B.; Hammerman, Cathy (American Journal of Perinatology, 2019)
Objective Intravenous lipid infusions improve both short- and long-term outcomes of premature neonates. However, prolonged infusion of lipids has been implicated in the development of parenteral nutrition-associated cholestasis (PNAC). We speculated that the multicomponent SMOFlipid would be hepatoprotective against PNAC.Study Design This is a retrospective review comparing the incidence and severity of direct hyperbilirubinemia in preterm infants <1,500 g who were hospitalized for a minimum of 2 weeks during a 20-month period in which all preterm infants on total parenteral nutrition (TPN) received fat as Lipofundin with the following 20-month period in which all preterm infants on TPN received SMOFlipid.Results Infants in the SMOFlipid period had a lower incidence of PNAC (6 vs. 13%; p = 0.022), lower peak direct bilirubin levels (3.2 vs. 7.1 mg/dL; p = 0.018), and a shorter length of stay (51 vs. 60 days; p = 0.019). The relative risk of developing direct hyperbilirubinemia during the Lipofundin period was 2.22 (1.1–4.3) as compared with period 1; p = 0.018; NNT-14.Conclusion SMOFlipid was hepatoprotective in our population of preterm neonates <1,500 g receiving long-term TPN as compared with those receiving Lipofundin, despite similar levels of exposure to both intravenous lipid load and duration in the two groups.
Keywords: perinatal nutrition; cholestasis; long chain polyunsaturated fatty acids